Application Of Kinetics – Thermodynamics Model And Adsorption Mechanisms For Inhibition Of Acid Corrosion On Mild Steel By Red Onion Peel Extract - Mansor, Nuramirah (Universiti Sains Malaysia, 2021)
The study of kinetics–thermodynamics parameters and adsorption isotherms of the inhibition of corrosion mild steel in acid medium using red onion peel extract (ROPE) as green corrosion inhibitor was carried out. The inhibition efficiency was found to increase with increasing inhibitor concentration but decrease with increasing temperature of acid medium because at higher temperature the mild steel is oxidized at higher rate and causing the inhibitor to desorb back from mild steel surface. The value for heat of adsorption, Qads ranged from -39.89 to -41.71 KJ.mol-1 indicates that the reaction is exothermic. The adsorption data fitted well to Langmuir adsorption isotherm model. Thermodynamic equations were used to determine the activation energy (Ea), enthalpy change (∆H) and entropy change (∆S). The adsorption isotherms such as Langmuir, Freundlich, Flory–Huggins, Temkin, and Frumkin were used to evaluate the change of Gibb’s free energy from the adsorption equilibrium constant, Kads, value. The adsorption of the inhibitor on surface of mild steel was found to be spontaneous and consistent with the physical adsorption mechanism as ∆Gads is negative value and less than -20 KJ.mol-1.